Hubungan Pengetahuan Tentang Menstruasi Dengan Sikap dalam Penatalaksanaan Dismenore Primer pada Remaja Putri di SMAN 58 Jakarta - Anggita Wijayanti; Refirman DJ; Sri Rahayu (Biota, 2017)
Primary dysmenorrhea was experienced by about 72.89 % of young women in Indonesia. Primary dysmenorrhea is a common problem that often reported during their cycle. In other study, there are about 41.2 % of young woman that choose to do nothing in order to reduce their pain. Therefore, knowledge about menstruation has big part for their attitude and practices to reduce and stop the pain caused by dysmenorrhea. This study aims to know the correlation between menstruation knowledge with attitude in the primary dysmenorrhea management. This study was done in November 2016 at SMAN 58 Jakarta, using descriptive method and correlation study survey technique. All of the class XII female student were used as the population, and 90 responden were taken using simple random sampling. The test showed that the data was homogen and have normal distribution. The regression model Y = 30.557 + 2.166X was significant and showed a linear correlation. Correlation coefficient obtained from hypothesis test was 0.762. This result showed a strong and positive correlation between knowledge and attitude about primary dysmenorrhea in female student at SMAN 58 Jakarta